FEATURES AND PROSPECTS FOR THE NANOCATALYSTS DEVELOPMENT - КИСЛОВА, О. В. (Technologies and Engineering, 2023)
Purpose. Summarize information about the structural features and properties of nanocatalysts, the principle of their action, efficiency, specificity, advantages of application and promising areas of development. Methodology. Analysis of literature data about the dependence of the nanoobjects catalytic properties on their spatial dimension, the influence of structural features on the nanocatalysis efficiency, development prospects. Findings. Nanocatalysts are characterized by a combination of specific physical and chemical properties due to a significant increase in the specific surface due to a particle size decrease, a change in the crystal structure and electronic levels structure. The mechanism of nanocatalysts action differs from classical catalysts action. The efficiency of catalysis is significantly affected by the size of nanoparticles and their interaction with the support. Nanocomposite materials based on metal nanoclusters and modified polyelectrolytes, carbon materials and zeolites, which stabilize the nanoobjects structure and increase their catalytic activity, are widely used. Originality. Literature data analysis have shown that the efficiency of nanocatalysts depends on the spatial dimension of nanoobjects and defects in their structure. The creation of composite nanomaterials stabilizes catalyst nanoparticles, preserves their unique properties and technologically modifies the organization of catalytic processes. Practical value. Nanocatalytic systems make it possible to implement chemical-technological processes with greater efficiency and lower energy consumption in accordance with environmental requirements. Modern methods for obtaining nanocatalysts with optimal structural and dimensional characteristics contribute to an increase in their activity, selectivity and cost reduction.